Upaya Peningkatan Pengetahuan Siswa Tentang Pentingnya Mitigasi Bencana di Desa Hutamonu, Kecamatan Botumoito, Kabupaten Boalemo - Ronal Hutagalung; Aang Panji Permana; Djamal Adi Nugroho Uno; Muh Nasrullah Al Fauzan; Aisyah Alya H Panai (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2022)
Indonesia is a country that has a high level of disaster risk. Community preparedness efforts, especially for children, are still lacking, marked by the number of victims of natural disasters which is still very high, with this effort increasing knowledge about disaster mitigation is still very important for the community. This service aims to increase public knowledge, especially students, about disaster mitigation efforts, through outreach activities in several schools. The results of the service show that the level of student knowledge about disaster mitigation is still very lacking and needs to be improved. It is hoped that further actions such as maintenance and supervision as control with the aim of these activities have optimal results to increase students' knowledge about disaster mitigation and the realization of disaster resilient schools.